2007
DOI: 10.1038/sj.jes.7500545
|View full text |Cite
|
Sign up to set email alerts
|

Bias and confounding in longitudinal measures of exhaled monoxides

Abstract: The measurement of exhaled nitric oxide and carbon monoxide concentrations is an emerging method of monitoring airway inflammation longitudinally in community-based studies. Inhaled concentrations of these monoxides influence exhaled concentrations. Little is known about the degree to which inhaled concentrations distort temporal trends in, or estimated effects of air pollutants on, exhaled monoxides. We sought to evaluate whether estimated effects of air pollutants on exhaled monoxides are distorted by trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Averaging times for the meteorologic variables were matched to the corresponding air pollutant variables of interest. Even though our eNO measurement method was designed to remove nitric oxide (NO) from inhaled air, in models predicting eNO we included control for indoor NO levels based on previous research supporting this approach ( Dorevitch et al 2007 ). Indoor NO levels were significant predictors of eNO, and associations between eNO and pollutant metrics were attenuated by 12% on average without indoor NO in the models; however, excluding indoor NO did not affect the overall significance of associations.…”
Section: Methodsmentioning
confidence: 99%
“…Averaging times for the meteorologic variables were matched to the corresponding air pollutant variables of interest. Even though our eNO measurement method was designed to remove nitric oxide (NO) from inhaled air, in models predicting eNO we included control for indoor NO levels based on previous research supporting this approach ( Dorevitch et al 2007 ). Indoor NO levels were significant predictors of eNO, and associations between eNO and pollutant metrics were attenuated by 12% on average without indoor NO in the models; however, excluding indoor NO did not affect the overall significance of associations.…”
Section: Methodsmentioning
confidence: 99%
“…319 In addition, environmental exposure to CO may affect eCO measurements, potentially giving falsely high results. 311,320 High ambient (e.g., near traffic) or indoor (e.g., secondhand smoke) CO concentrations should be avoided where eCO is being measured.…”
Section: Respiratory End Pointsmentioning
confidence: 99%
“…The number of cigarettes smoked, the inhalation of tobacco smoke and the CO levels measured inside the apartments were significant predictors of the CO exhaled levels. Dorevitch et al (2007) evaluated the levels of CO exhaled by 27 subjects who are the residents of public housing and concluded that exhaled concentrations were more strongly associated with indoor than with outdoor concentrations [33]. Approximately half of the variability in exhaled monoxide concentrations over time can be explained by changes in indoor monoxide concentrations.…”
Section: Personal Co Exposurementioning
confidence: 99%